Dual-Modal Photoacoustic Imaging and Optical Coherence Tomography [Review] - Hosseinaee, Zohreh; Tummon Simmons, James A.; Reza, Parsin Haji (Frontiers in Physics, 2021)
Optical imaging technologies have enabled outstanding analysis of biomedical tissues through providing detailed functional and morphological contrast. Leveraging the valuable information provided by these modalities can help us build an understanding of tissues’ characteristics. Among various optical imaging technologies, photoacoustic imaging (PAI) and optical coherence tomography (OCT) naturally complement each other in terms of contrast mechanism, penetration depth, and spatial resolution. The rich and unique molecular-specified absorption contrast offered by PAI would be well complemented by detailed scattering information of OCT. Together these two powerful imaging modalities can extract important characteristic of tissue such as depth-dependent scattering profile, volumetric structural information, chromophore concentration, flow velocity, polarization properties, and temperature distribution map. As a result, multimodal PAI-OCT imaging could impact a broad range of clinical and preclinical imaging applications including but not limited to oncology, neurology, dermatology, and ophthalmology. This review provides an overview of the technical specs of existing dual-modal PAI-OCT imaging systems, their applications, limitations, and future directions.